ANALISIS KELAYAKAN FINANSIAL SAYUR HIDROPONIK METODE RAKIT APUNG DI OXYGEN FARM SINGOSARI MALANG - kholis, Nur; Relawati, Rahayu; Baroh, Istis (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Global population growth and climate change have sparked interest in efficient and sustainable agricultural innovations. This research proposes a financial feasibility analysis for implementing hydroponic vegetable farming using the floating raft method at Oxigen Farm, Singosari, Malang. Leveraging modern technology, this study aims to evaluate the economic sustainability and contribution to the growth of the agricultural sector amid the pressing limitations of arable land. The floating raft method was chosen to enhance land use efficiency and control the environmental conditions for plant growth. The financial analysis covers investment costs, income projections, and profits over a specified period. The analysis of investment costs and income projections reveals promising profit potential, indicating that the investment has good financial feasibility. Meeting investment criteria, including a positive Net Present Value (NPV) of Rp. 43.04, a Gross Benefit/Cost (BC) ratio of 1.16, a Net B/C ratio of 2.18, and an Internal Rate of Return (IRR) exceeding the utilized interest rate at 54,59%, supports the conclusion that the business is viable. The findings support the view that implementing the floating raft method in hydroponic farming in Singosari, Malang, could provide a sustainable solution to the critical challenge of agricultural land conversion. Implications include the potential development of efficient and sustainable modern farming models, contributing positively to the local economy and food resilience.